Виклики штучного інтелекту для прав людини - Канцір, Р. Б. (ХНУРЕ, 2023)
This article looks at the negative impact that artificial intelligence has on human rights. The analysis highlights possible violations of privacy, discrimination, and employment rights caused by artificial intelligence. The study emphasizes the importance of developing ethical norms and legislation to protect human rights in the context of artificial intelligence.